Supervision Management Of Supervisor Managerial In Improving Performance Head Of Madrasah Tsanawiyah In Bandung District - Supriatna, Ade; Ulfiah, Ulfiah; Koswara, Nandang; Muhamad Rifki Noval, Sayid (CV. Inara, 2022)
Facing the demands of improving the quality of education, an important component that should not be ignored is the Head of Madrasah. Madrasah principals are required to have managerial competence in managing madrasas. The competence of the Madrasah Head can be carried out properly, one of which is supported by the guidance carried out by the education supervisor through a managerial supervision program. Therefore, the focus of this research is the management of supervisory managerial supervision in improving the performance of the head of MTs in the Ministry of Religion of Bandung Regency so that the expected output is increasing the quality of managerial supervision of Madrasah Tsanawiyah (MTs) supervisors, especially Madrasah Tsanawiyah Supervisors (MTs) Darussalam Arjasari, Madrasah Tsanawiyah ( MTs) Al-Ihsan Ciparay and Madrasah Tsanawiyah (MTs) Al-Matsur Pamengpeuk. This study aims to analyze and find empirically about the management of managerial supervision carried out by MTs Supervisors in improving the performance of the head of Madrasah Tsanawiyah (MTs) in the Ministry of Religion of Bandung Regency. The research process is carried out through the identification of phenomena that occur in planning, implementing, organizing, monitoring, impacting, supporting factors and obstacles to managerial supervision of the madrasah principal. The respondents were Supervisor, Head of Madrasah and Head of Madrasah Section, Ministry of Religion, Bandung Regency. The results of his research that the implementation of managerial supervision carried out by the supervisor of MTs Darusalam, Al-Ihsan, Al-Mansur can affect the performance of the madrasa principal. The supporting factor is the good relationship between the MTs Supervisor and the Head of Madrasah Tsanawiyah. The obstacles to managerial supervision are the lack of coordination between supervisors and the Madrasah Section and the supervisor's role is not functioning optimally. The solutions are: the supervisor's role as a partner, partner, motivator, negotiator, consultant, innovator, evaluator, the conclusion is that: First, supervisors carry out supervision to improve and improve the performance of the Head of Madrasah Tsanawiyah starting with planning, implementation to evaluation. Both supervisions are carried out to monitor, improve programs, and carry out follow-up supervision for the realization of improving the performance of madrasah principals so that they are motivated to advance education. The research product is a coordination forum between the head of the madrasah section or the Head of the Ministry of Religion with the Supervisor and Supervisory Assessment with the PKPM program (Performance Assessment of Madrasah Supervisors).